Escalating Dose Antigen Specific Therapy with dsDNA Injection Regulate Balance Ratio of Inflammatory Cells in Pristane-Induced Lupus Mice Model - sri poeranto (Stem Cell Research and Development Center, Universitas Airlangga, 2019)
Immunosuppressant and steroid therapy for SLE have not shown satisfactory results. Another method of therapy that is being developed is vaccines and escalating dose immunotherapy using self-antigen. The aim of this study was to assess the balance of immune cells through the ratio of pro-inflammatory and anti-inflammatory cells and cytokines in SLE using self-antigen dsDNA therapy. Methods: Female Balb/c mice 6-8 weeks old separated randomly to negative control group and pristane induced lupus (PIL) mice group. PIL mice groups were injected pristane intraperitoneally. Twelve weeks after the injection, the mice were evaluated for clinical and serological manifestations (anti-dsDNA levels). Mice with lupus signs were divided into four groups; positive control group: PIL mice without EDI dsDNA therapy, treatment A: PIL mice with EDI dsDNA therapy dose I (0.01μg/ml, 0.1μg/ml, 1μg/ml), treatment B: PIL mice with EDI dsDNA therapy dose II (0.1μg/ml, 1μg/ml, 10μg/ml), and treatment C: PIL mice with EDI dsDNA therapy dose III (1μg/ml, 10μg/ml, 100μg/ml). dsDNA were injected once a week and the dose was increased every week. Samples were analyzed for active/inactive dendritic cells ratio, Th1/Th2 cells ratio, Th17/Treg cells ratio and IL-17/TGF-β levels ratio. Results: Escalating dose antigen specific therapy with dsDNA injection of third dose reduced active/inactive dendritic cells ratio (p=0.000), Th1/Th2 cells ratio (p=0.010), Th17/Treg ratio (p=0.004) and decrease IL-17/TGF- β levels ratio (p=0.004) significantly compared to positive control. Conclusion: Escalating dose antigen specific therapy with dsDNA injection of dose III was able to regulate balance ratio of inflammatory cells and cytokines in PIL mice thus the immune tolerance may improve compared to control groups.